Misoprostol for Treatment of Incomplete Abortions by Gynecologists in Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:Misoprostol is approved for treatment of incomplete abortion in Nigeria, but subjective evidence suggests that it is seldom used by gynecologists in Nigeria for this indication. The purpose of the study was to determine the rate of utilization of misoprostol for treatment of incomplete abortion by gynecologists in Nigeria and perceived barriers to its use for this indication.Materials and Methods:This was a cross-sectional study of gynecologists who attended the 2017 Society of Gynaecology and Obstetrics of Nigeria, Conference held in Sokoto state, Nigeria as well as a retrospective review of Post abortion care services in three Nigerian tertiary hospitals for a period of one year (1 January-31 December, 2017).Results:Misoprostol was used in the treatment of first trimester abortions in 19/343 (5.5%) compared to manual vacuum aspiration (MVA) 324/343 (94.5%) in the tertiary hospitals. The major perceived barrier in the utilization of misoprostol for treatment of first trimester incomplete abortion was the preference of MVA to misoprostol by the provider (32%) and was followed closely by not being sure of the brand of the misoprostol (31%). Other reasons included that misoprostol was not effective (6%), side effects (8%), high cost (5%), unavailability (1%), not conversant with dosage regimens (1%), and others (16%). Overall, 51% of responders confirmed that they do not have a written onsite protocol for the management of first trimester incomplete abortions in their institutions.Conclusions:There is poor utilization of misoprostol, barriers to its use, and absence of protocols/guidelines for the treatment of first trimester incomplete abortions in most gynecological departments of Nigeria’s public health institutions. It is expedient for gynecologists in Nigeria to put in place processes that ensures translation of evidence-based research findings into practice and policies towards improving maternal health in Nigeria.